THE EFFECT OF SOFT SKILLS AND HARD SKILLS ON THE WORK READINESS OF GRADE XII STUDENTS - Nur Fitri Intan Sari; Maharani Rahma (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to determine the effect of soft skills and hard skills on the work readiness of 12th-grade students at SMK Mahardika Batujajar. This study used a quantitative approach with a survey method. The population in this study was all 467 12th-grade students at SMK Mahardika Batujajar. The sample size was determined using the Chocran formula with a 10% error rate, resulting in a sample size of 86 respondents. The sampling technique used was simple random sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis with the help of SPSS version 24. The results showed that soft skills partially had a positive and significant effect on students' work readiness, with a calculated t-value of 2.493, which is greater than the t-table of 1.989, and a significance level of 0.015, which is less than 0.05. Hard skills also have a positive and significant effect on students' work readiness, with a calculated t value of 6.597 which is greater than the t table of 1.989 and a significance level of 0.000 which is smaller than 0.05. Simultaneously, soft skills and hard skills have a significant effect on students' work readiness, with a calculated F value of 144.949 which is greater than the F table of 3.11 and a significance level of 0.000 which is smaller than 0.05. The coefficient of determination value of 0.772 indicates that 77.2% of the variation in students' work readiness can be explained by soft skills and hard skills, while the remaining 22.8% is influenced by other factors outside this study.